CLINICAL AND PATHOPHYSIOLOGICAL SPECIFICITIES OF ATHEROSCLEROSIS IN PATIENTS WITH TYPE 2 DIABETES - Maciej Kosiński; Martyna Strzemkowska; Mariusz Dotka; Kinga Brzezińska (International Journal of Innovative Technologies in Social Science, 2025)
Research objectives: Type 2 diabetes mellitus significantly increases the risk of developing atherosclerosis and cardiovascular complications. Cardiovascular diseases are the leading cause of death in this patient population; however, diagnosis is often delayed due to the potential for atypical clinical presentation. The purpose of this review is to present the specific clinical and pathophysiological features of atherosclerosis in patients with type 2 diabetes mellitus, with particular emphasis on the distinct mechanisms of atherosclerotic development in these patients, as well as diagnostic and prognostic differences. Key findings: In the course of type 2 diabetes mellitus, atherosclerosis develops against a background of chronic metabolic disturbances such as hyperglycemia, insulin resistance, dyslipidemia, and chronic inflammation. Patients often present with atypical or minimal symptoms, which complicates early diagnosis. Standard cardiovascular risk assessment tools may underestimate the actual threat in this group. Current research is exploring the use of novel biomarkers and imaging techniques to improve the precision of risk stratification. Summary (conclusions): Atherosclerosis in type 2 diabetes mellitus is characterized by a distinct clinical and biological profile. Understanding these differences is essential for earlier diagnosis, more accurate risk assessment, and more effective cardiovascular prevention in this high-risk patient population.